2016
DOI: 10.1097/dcr.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Specific Extraction-Site Location on the Risk of Incisional Hernia After Laparoscopic Colorectal Resection

Abstract: Preferential extraction sites to minimize incisional hernia rates should be Pfannenstiel or incisions off the midline. Midline incisions should be avoided when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
71
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 28 publications
15
71
2
6
Order By: Relevance
“…Based on computed tomographic finding, the incidence of overall incisional hernia of the SES in the present study was 21.6% in the midline group and 26.4% in the transverse group. Although the incisional hernia rate in the SES in our study was higher than that reported in a previous study [25] of incisional hernia rate of approximately 10% in low midline or low transverse incision, it is presumed that the specimen of 50% or more of patients was extracted via the temporary stoma site, which may be a risk factor of incisional hernia after temporary stoma closure [25,26]. However, the comparable incisional hernia rates after LRCS between the two groups in our study was somewhat different from that reported in a systematic review [10], which reported that the incisional hernia rate in midline incision was three times higher than that in transverse incision.…”
Section: A C C E P T E D a R T I C L Econtrasting
confidence: 90%
See 2 more Smart Citations
“…Based on computed tomographic finding, the incidence of overall incisional hernia of the SES in the present study was 21.6% in the midline group and 26.4% in the transverse group. Although the incisional hernia rate in the SES in our study was higher than that reported in a previous study [25] of incisional hernia rate of approximately 10% in low midline or low transverse incision, it is presumed that the specimen of 50% or more of patients was extracted via the temporary stoma site, which may be a risk factor of incisional hernia after temporary stoma closure [25,26]. However, the comparable incisional hernia rates after LRCS between the two groups in our study was somewhat different from that reported in a systematic review [10], which reported that the incisional hernia rate in midline incision was three times higher than that in transverse incision.…”
Section: A C C E P T E D a R T I C L Econtrasting
confidence: 90%
“…In concordance with this study, our results demonstrated an incisional hernia rate of 37% in patients in whom mini-laparotomy is used for synchronous temporary stoma formation compared with that of 6% in the patients in whom mini-laparotomy is only used for specimen extraction (p<0.001). However, when the SES is not used for temporary stoma, our incisional hernia rates of the SES were 7.1% and 4.0% in the low midline and low transverse incisions, respectively, (p=0.507), and these results are similar to those of previous studies reporting an incisional hernia rate of approximately 10% in low midline incision and approximately 4% in low transverse incision following LRCS [25,28,29]. Based on these results, with respect to incisional hernia, low midline incision, if not used for temporary stoma formation, may be used as the SES as low transverse incision during LRCS.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 89%
See 1 more Smart Citation
“…Compared to the rigid instruments used in classical laparoscopy, the angled arms of robot offer a great advantage of multidirectional mobility to surgeon when creating intracorporeal anastomosis. We prefer the suprapubic incision for specimen extraction since this incision is associated with better cosmetic outcomes, less pain, and hernia risk (7,21,23).…”
Section: Difficultymentioning
confidence: 99%
“…In Relation zum Pfannenstiel-Schnitt waren Mittellinieninzisionen mit einer 10-13-fach erhöhten Narbenhernieninzidenz verbunden. In der Synopsis ist mit einer Narbenhernienrate nach Mittellinien-, queren und Pfannenstiel-Inzisionen in 10,6, 3,7 und 0,9 % zu rechnen [10].…”
Section: Status Quo Des Faszienverschlussesunclassified